Inovações da nova lei geral de licitações : um estudo sobre os impactos da Lei nº 14.133/2021 nas licitações públicas no Instituto Federal do Espírito Santo - IFES - Alves Junior, Arisio Wingler (2024)
The efficient and transparent management of public policies, especially in the context of government procurement, is a constant challenge, intensified by the need to meet growing demands with fiscal responsibility. Public procurement is the legal procedure for contracting goods and services by government institutions, which play a significant role as major consumers of public resources. With the enactment of the New Law on Public Procurement and Contracts (Law No. 14,133/2021), several mandatory innovations were introduced in all spheres of government, standing out as a transformation of great relevance to public administration. Given this context, the central problem investigated is: what are the concrete impacts of the changes promoted by the new legislation on the bidding processes of the Instituto Federal do Espírito Santo (Ifes)? The main objective was to identify the changes brought about by Law No. 14,133/2021 and analyze their impacts on the efficiency, security, and agility of the procurement processes, as well as to understand the training demands of the public servants involved. In theoretical terms, the research was based on the concepts of public governance, administrative efficiency and government procurement management, based on contemporary theoretical contributions on public bidding and administrative contracts. Regarding the methods and procedures, a qualitative and descriptive approach was adopted, with data collection through a questionnaire applied to Ifes contracting agents. The analysis was carried out based on the Critical Incident Technique, which allowed for the identification of challenges and good practices in the implementation of the new legislation. The results obtained include a detailed understanding of the impacts of the legislative changes in the context of Ifes, highlighting advances such as the implementation of the principles of governance and transparency, the virtualization of bidding processes, increasing efficiency and accessibility and the need for specific training focused on the operationalization of processes and the use of digital tools. As a technical/technological product, practical training was developed for employees, aiming to support the efficient implementation of the new legislation and foster the responsible management of public resources